Community Rights Protection as a Pillar of Suistainable Mining in INdonesia : A Review of Government and CSR Roles From Environmental Law and Islamic Environmental Jurisprudence - Niken Yulian Yusuf; Maskun Maskun; Arfin Hamid; Muhammad Mutawalli Mukhlis; Nurul Hidayat Ab Rahman (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2025)
Sustainable mining in Indonesia requires balancing economic extraction with environmental protection and community rights. However, current frameworks—government regulation and mandatory CSR—often face implementation gaps and lack ethical grounding. This study examines how integrating Islamic environmental jurisprudence with Indonesia’s environmental law and CSR obligations can better protect community rights and promote sustainable mining practices. Using a normative empirical legal approach, the study analyzes Scopus-indexed literature, statutory instruments (e.g., Law No. 32/2009), and Islamic legal sources. It maps conventional mechanisms such as land-right recognition, FPIC, regulatory oversight, and CSR, and extends the analysis with: (1) a comparative integration of government and CSR roles with Islamic principles (amanah, ʿadl, ḥifẓ al-bi’ah), and (2) case studies from Bangka Belitung and other mining regions showing faith-based community mobilization. Findings show that coupling legal mechanisms with Islamic ethical imperatives enhances community agency: government policies gain moral legitimacy, CSR becomes a faith-driven commitment, and communities use fatwas and customary-Islamic norms to demand environmental justice and corporate accountability. Evidence shows regions applying Islamic fatwas on “environmentally friendly mining” benefit from stronger social licenses and improved local welfare. This study contributes an integrative governance model that combines legal obligations, CSR practices, and Islamic ethics to prioritize community rights and ecological sustainability in Indonesia’s mining sector.